Problems of increase of efficiency of protection of the labor law of citizens means of public prosecutor’s activity - Шандула, О. О. (Theory and practice of jurisprudence, 2016)
Problems of the organization and implementation of public prosecutor’s activity in the sphere of protection of the labor law of citizens are considered. The legal nature and the main components of this activity is defined. The technique of public prosecutor’s activity on each separate direction of protection of the labor law of citizens reveals. Prospects of protection of the labor law of citizens by means of public prosecutor’s activity in a context of reforming of the legislation on prosecutor’s office are estimated.